High lipoprotein(a) as a possible cause of clinical familial hypercholesterolaemia: a prospective cohort study - Langsted, Anne; Kamstrup, Pia R; Benn, Marianne; Tybjærg-Hansen, Anne; Nordestgaard, Børge G (The lancet. Diabetes & endocrinology, 2016)
The reason why lipoprotein(a) concentrations are raised in individuals with clinical familial hypercholesterolaemia is unclear. We tested the hypotheses that high lipoprotein(a) cholesterol and LPA risk genotypes are a possible cause of clinical familial hypercholesterolaemia, and that individuals with both high lipoprotein(a) concentrations and clinical familial hypercholesterolaemia have the highest risk of myocardial infarction. We did a prospective cohort study that included data from 46 200 individuals from the Copenhagen General Population Study who had lipoprotein(a) measurements and were genotyped for common familial hypercholesterolaemia mutations. Individuals receiving cholesterol-lowering drugs had their concentrations of LDL and total cholesterol multiplied by 1·43, corresponding to an estimated 30% reduction in LDL cholesterol from the treatment. In lipoprotein(a) cholesterol-adjusted analyses, total cholesterol and LDL cholesterol were adjusted for the lipoprotein(a) cholesterol content by subtracting 30% of the individuals' lipoprotein(a) total mass before total and LDL cholesterol were used for diagnosis of clinical familial hypercholesterolaemia. We used modified Dutch Lipid Clinic Network (DLCN), Simon Broome, and Make Early Diagnosis to Prevent Early Death (MEDPED) criteria to clinically diagnose familial hypercholesterolaemia. Cox proportional hazard regression calculated hazard ratios (95% CI) of myocardial infarction. Using unadjusted LDL cholesterol, mean lipoprotein(a) concentrations were 23 mg/dL in individuals unlikely to have familial hypercholesterolaemia, 32 mg/dL in those with possible familial hypercholesterolaemia, and 35 mg/dL in those with probable or definite familial hypercholesterolaemia (ptrend<0·0001). However, when adjusting LDL cholesterol for lipoprotein(a) cholesterol content the corresponding values were 24 mg/dL for individuals unlikely to have familial hypercholesterolaemia, 22 mg/dL for those with possible familial hypercholesterolaemia, and 21 mg/dL for those with probable or definite familial hypercholesterolaemia (ptrend=0·46). High lipoprotein(a) cholesterol accounted for a quarter of all individuals diagnosed with clinical familial hypercholesterolaemia and LPA risk genotypes were more frequent in clinical familial hypercholesterolaemia, whereas lipoprotein(a) concentrations were similar in those with and without familial hypercholesterolaemia mutations. The hazard ratios (HRs) for myocardial infarction compared with individuals unlikely to have familial hypercholesterolaemia and lipoprotein(a) concentration of 50 mg/dL or less were 1·4 (95% CI 1·1–1·7) in those unlikely to have familial hypercholesterolaemia and lipoprotein(a) concentrations of more than 50 mg/dL, 3·2 (2·5–4·1) in those with possible, probable, or definite familial hypercholesterolaemia and lipoprotein(a) concentration of 50 mg/dL or less, and 5·3 (3·6–7·6) in those with possible, probable, or definite familial hypercholesterolaemia and lipoprotein(a) concentration of more than 50 mg/dL. In analyses using Simon Broome or MEDPED criteria, results were similar to those using DLCN criteria to diagnose clinical familial hypercholesterolaemia. High lipoprotein(a) concentrations and corresponding LPA risk genotypes represent novel risk factors for clinical familial hypercholesterolaemia. Our findings suggest that all individuals with familial hypercholesterolaemia should have their lipoprotein(a) measured in order to identify those with the highest concentrations, and as a result, the highest risk of myocardial infarction. Danish Heart Association and IMK General Fund, Denmark.